The response of broilers during three periods of growth to dietary valine - Ferreira, Nayara Tavares [UNESP]; Albuquerque, Ricardo de; Sakomura, Nilva Kazue [UNESP]; Dorigam, Juliano César de Paula [UNESP]; Silva, Edney Pereira da [UNESP]; Burbarelli, Maria Fernanda C.; Ferreira, João Guilherme; Gous, Robert Mervyn (Elsevier, 2016)
In diets based on corn and soybean meal valine is considered the fourth limiting amino acid. Despite that, there have been few studies to date on the response of broilers to dietary valine and most of them use empirical procedures leading to a great variation in the recommendations. Thus, the aim of this study was to quantify the performance and body composition of broiler chickens subjected to different intakes of digestible valine using the dilution technique. Three trials were conducted separately with Cobb 500 broilers in the starter (1-14 days), grower (14-28 days) and finisher phase (28-42 days). In the starter and grower phases, the birds were distributed in a completely randomized design with eight treatments (seven levels of valine and a control treatment), with seven replicates, each consisting of 12 birds for starter and grower phases while 10 birds were used in the finisher phase. Basal diets were formulated by dilution technique, being one summit diet with valine as the first limiting amino acid and diluted with a nitrogen-free diet to obtain the intermediary levels. Valine intake for maximum weight gain, valine deposition, and protein deposition in the defeathered body and feather were estimated with broken-line models. Body fat content was calculated with linear regressions. Results indicate that to maximize performance of broiler chickens across several parameters, the recommended requirement of digestible valine for the starter, grower and finisher diet is 226, 637 and 1231 mg/bird/day, respectively. These recommendations allow achieving optimum performance in the broiler production system but they can be different depending on way birds are sold (whole chicken or cut-up) and age of the birds at slaughter.
Keywords: Broken-line; Relative response; Requirement; Valine deposition